Malignancy in autoimmune diseases. - Kinlen, L (1992)
Rheumatoid arthritis (RA) represents the autoimmune disease that has been most studied in relation to malignancy. An examination of all published cohort studies has indicated a 9.7-fold increase of non-Hodgkin's lymphoma among RA patients after immunosuppressive therapy, and a 2.5-fold increase in the absence of such treatment. Corresponding data for Sjögren's syndrome point to a similar contrast. These findings are inseparable from the hypothesis of impaired immunosurveillance which implies that malignancy is promoted by defects in the immune system. Studies of individuals treated with immunosuppressive drugs, particularly to prevent graft rejection, have indicated that immunosurveillance operates only against a restricted range of neoplasms. These include non-Hodgkin's lymphoma (NHL), squamous cell skin cancer, Kaposi's sarcoma and cervical carcinoma. Other states of immune impairment including AIDS are also associated with marked increases of NHL. There is a striking correspondence between malignancies for which there is epidemiological or laboratory evidence for a virus aetiology and those that are increased by immune impairment. In this respect the epidemiological evidence accords with experimental work that immunosurveillance primarily operates against neoplasms of viral origin. It is therefore possible that a viral aetiology also underlies the excess of NHL in certain autoimmune disorders, particularly after immunosuppressive therapy.